Expressive Speech Act in Comments on Instagram BBC Arabic - Fitriyah, Tika; Nashoih, Afif Kholisun; Fajar, Qoyyumul; Barkah, Salima Muhammad Husain (Universitas Islam Negeri Raden Intan Lampung, 2022)
A language reflects the culture of the speakers. The use of language on social media platforms without an editor creates several issues, one of which is that it can spiral out of control. The goal of this research is to categorize and analyze expressive speech acts of praise and criticism in BBC Arabic Instagram comments. This is a descriptive-qualitative study with data sources in the form of netizen comments on BBC Arabic between January and February. There are two hundred data in total and they were obtained using a purposive sample technique. According to the findings of this research, many users of social media express criticism more often than they express praise or appreciation, with a ratio of 87:13. Being outspoken in their criticism will become the character and culture of social media users over time. This is clearly not in line with Arab culture, where Islam is the dominant religion. As a result, that was expected that research based on this model will be able to influence how language is used on social media.